إدارة الصراع التنظيمي وعلاقته بتقدير الذات لدى الموظفين الإداريين بجامعة عمار ثليجي الأغواط (كلية العلوم الاجتماعية - بن الزبير عبد الرحمان; بوسماحة يوسف; صافي محمد (My University, 2021)
The study aimed to identify the relationship of self-esteem and management of organizational conflict among employees and employees at Ammar Thligan University in Ghouta, where the sample of the study included (40) employees. To process the results, we used appropriate statistical means to identify the relationship. After statistical analysis, we concluded that there was a relationship between self-esteem and the management of organizational conflic